2013
DOI: 10.1146/annurev-biochem-072711-164732
|View full text |Cite
|
Sign up to set email alerts
|

Signal Recognition Particle: An Essential Protein-Targeting Machine

Abstract: The signal recognition particle (SRP) and its receptor comprise a universally conserved and essential cellular machinery that couples the synthesis of nascent proteins to their proper membrane localization. The past decade has witnessed an explosion in in-depth mechanistic investigations of this targeting machine at increasingly higher resolution. In this review, we summarize recent work that elucidates how the SRP and SRP receptor interact with the cargo protein and the target membrane, respectively, and how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
353
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 400 publications
(360 citation statements)
references
References 234 publications
(294 reference statements)
6
353
0
1
Order By: Relevance
“…According to the classical viewpoint, cotranslational ER targeting of secretory proteins is accomplished by translational pausing after the recognition of a signal sequence by SRP (2,3). This process enables the nascent polypeptide to recruit its own mRNA to the ER.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the classical viewpoint, cotranslational ER targeting of secretory proteins is accomplished by translational pausing after the recognition of a signal sequence by SRP (2,3). This process enables the nascent polypeptide to recruit its own mRNA to the ER.…”
Section: Discussionmentioning
confidence: 99%
“…In eukaryotes, secretory proteins are initially translated by cytosolic ribosomes. When the N-terminal signal peptide reaches outside of the peptide exit channel in the ribosome, the ribosome nascent chain (RNC) complex is recognized by the signal recognition particle (SRP) and peptide elongation is slowed (1)(2)(3)(4)(5). This SRP-RNC complex is then recruited to the ER via the affinity between SRP and SRP receptor (SR) that exists in the ER membrane (2, 3).…”
mentioning
confidence: 99%
“…1A). Both SRP and SRP receptor (called FtsY in bacteria) also contain a conserved NG domain, comprised of a GTPase (guanosine 5′-triphosphate hydrolase) G domain and the N domain, whose direct interaction mediates the delivery of cargo to the target membrane.Biophysical analyses (32)(33)(34) showed that membrane targeting is a two-step process in which SRP and FtsY first associate via their N domains to form a transient early intermediate (31,32,35). GTP (guanosine 5′-triphosphate)-driven rearrangements then bring the G domains of both proteins into close contact, giving a stable closed complex (36,37).…”
mentioning
confidence: 99%
“…SRP is a universally conserved ribonucleoprotein complex responsible for the cotranslational targeting of proteins to the eukaryotic endoplasmic reticulum (ER), or the bacterial plasma membrane (31). SRP recognizes ribosome-nascent chain complexes (termed RNC or cargo) carrying strong signal sequences and delivers them to the SecYEG or YidC translocation machinery on the target membrane.…”
mentioning
confidence: 99%
“…The signal peptide (pre-peptide) of a KLK polypeptide emerging from a ribosome is bound by the signal recognition particle (SRP), which results in delayed translation and association with a membrane-bound SRP receptor (Akopian et al, 2013). Subsequently, this complex assembles with the Sec complex of the rough endoplasmic reticulum (ER) and the elongating polypeptide inserts into the Sec61 transmembrane channel (Deshaies et al, 1991;Nyathi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%